Sistem Penjualan Produk Kecantikan Berbasis Web - Okka Raisa Lestari; Sintia (Journal of Applied Accounting And Business, 2020)
The manual sales method is still widely used by traders in Indonesia, one of which is the Home Shopping Jambi store, a shop that sells a variety of beauty products. To reach more customers and provide clear information about the product, we need a media that is able to provide information. This makes the writer realize that the role of website and internet media can process sales and market beauty products that are sold in Home Shopping Jambi stores easily. The data collection method used by the author as the basis for writing the report is by direct observation to the store and interview. This research resulted in a web-based sales system called e-commerce. Electronic Commerce (e-commerce) is the process of buying, selling or exchanging products, services and information through a computer network. The programming technique used in making the Home Shopping Jambi web-based application store is the PHP programming language and MySQL database. This application provides information to customers about products and stock items sold by Home Shopping Jambi stores easily and quickly